Platelet distribution width is highly associated with thrombotic events in primary antiphospholipid syndrome - Shi, Yu; Jiang, Hui; Huang, Can; Hu, Chaojun; Zhao, Jiuliang; Li, Mengtao; Zeng, Xiaofeng (Clinical rheumatology, 2021)
Objective Platelet activation is a possible pathogenic process contributing to thromboembolism in antiphospholipid syndrome (APS), and platelet distribution width (PDW) is associated with platelet activation. The objective of this study was to evaluate the association between platelet indices and thrombotic events in patients with primary APS. Methods This single-center cross-sectional study included 207 consecutive patients with APS treated at our institution between 2010 and 2019. Results of blood tests were recorded retrospectively from medical records. Results Of the included patients, 135 (65.2%) were female and 72 (34.8%) were male. They were classified into thrombotic ( n = 150) or non-thrombotic ( n = 57) groups. PDW, mean platelet volume, and large platelet ratio were significantly higher in the thrombotic group. In univariate logistic analysis, PDW was significantly associated with an increased odds of thrombosis [odds ratio (OR) 1.554, 95% confidence interval (CI) 1.289–1.873, p <0.001]. In multivariate logistic analysis, PDW and positive lupus anticoagulant (LA) were risk factors for thrombosis. Receiver operating characteristic analysis showed that PDW, combined with a positive LA, was a reliable indicator of thrombosis, with an area under the curve of 0.796 (95% CI 0.728–0.864). The optimal cutoff value for PDW was 12.4 fl, with a sensitivity of 72.0% and specificity of 77.2%. Multivariate logistic regression of PDW tertiles showed that the odds of thrombosis increased abruptly in the highest tertile. Conclusion This study confirmed the association between PDW and thrombotic events in APS patients, supporting the theory that platelet activation is a crucial mechanism of thrombosis in APS. Key Points • This study is the first to discuss the correlation between PDW and thromboses in patients with APS. • This study provides evidence of the important role of platelet activation in the pathogenesis of APS.